Peranan Teknologi Informasi Komunikasi Sebagai Media Pelayanan di Perpustakaan INSTIDLA - Eni Amaliah; Muhamad Bisri Mustofa; Mezan El Khaeri Kesuma; Siti Wuryan; Dedeh Ramadaniah; Sella Desti Tamara (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This Study aims to describe role of Information Communication Technology (ICT) as a Library Service Media began to be carried out by the Diniyyah Lampung Institute of Technology and Science (INSTIDLA) as a form of adjustment to the development and needs of students in the current era of Society 5.0. This study aims to determine the influence of information and communication technology on INSTIDLA library services. This research uses a qualitative method with an analytical descriptive approach where the role of ICT is explained comprehensively in the INSTIDLA Library as a Library Service Media. Data collection techniques use observation and interviews. The object of this study is instidla's library and social media services. INSTIDLA Library Services is a combination of manual services and information and communication technology (ICT) based services that support library professionalism in improving INSTIDLA library services. The result of this study is a significant influence between the development of ICT and library services through social media, including helping and facilitating the work of library staff, attracting visitors to the library, and facilitating the communication of librarians with library visitors and finally, the library information base via social media